A PTH/PTHrP receptor antagonist blocks the hypercalcemic response to estradiol-17b - Fuentes, J. (2012)
Estradiol (E2) increases circulating calcium and phosphate levels in fish, thus acting as a hypercalcemic and hyperphosphatemic factor during periods of high calcium requirements, such as during vitellogenesis. Since parathyroid hormone (PTH)-related protein (PTHrP) has been shown to be calciotropic in fish, we hypothesized that the two hormones could be mediating the same process. Sea bream (Sparus auratus) juveniles receiving a single intraperitoneal injection of piscine PTHrP(1-34) showed an elevation in calcium plasma levels within 24 h. In contrast, injections of the PTH/PTHrP receptor antagonist PTHrP(7-34) decreased circulating levels of calcium in the same period. Intraperitoneal implants of estradiol-17 (E2; 10 g/g) evoked significant increases of circulating plasma levels of calcium and phosphorus and a sustained increases of circulating plasma levels of PTHrP. However, a combined treatment of E2 and PTHrP(7-34) evoked a markedly lower calcium response compared with E2 alone. We conclude that PTHrP or a related peptide that binds the PTH/PTHrP receptor mediates, at least in part, the hypercalcemic effect of E2 in calcium and phosphate balance in fish.